Islamic Educational Psychology; Urgency and Distinction In The Islamic Religious Education Doctoral Program at UIN Ar-Raniry - Syatria Adymas Pranajaya; Warul Walidin; Salami Salami (Sustainable, 2023)
In the realm of Islamic education, the study of educational psychology which is still struggling to elevate the existence of Islamic labeled scholarship continues to be fought for, especially Islamic educational psychology which provides its dimension to the development of the world of education with spiritual-divine characteristics. UIN Ar-Raniry took part in this role, so it is also important to track the urgency and distinction of Islamic educational psychology at UIN Ar-Raniry. The purpose of writing this study article is to critically describe developments and strengthen the treasures of Islamic educational psychology in the world of Islamic education. The method in this study is library research with thematic analysis techniques. The results of this study indicate that UIN Ar-Raniry has made a real contribution to the development of Islamic educational psychology, by making psychological studies Islamic education a compulsory subject that must be taken by students of the Islamic Religious Education (PAI) Doctoral Program at UIN Ar-Raniry Banda Aceh. This has been carried out with a special urgency and distinction study. The distinction indicators of this subject correspond to the achievement of targeted learning graduates from the realm of attitudes, knowledge, general skills, and specific skills with 16 specific sub-studies given in this subject. The implications of this article are expected to encourage the improvement and development of the quality of Islamic educational psychology scientific studies in giving birth to the best generation of people and nation, and in the long term could transform into an accredited study program.